The Role of Nurses in Palliative and End-of-Life Care: A Review of Best Practices - Minu S.R (AG Volumes, 2025)
The spiritual, emotional, and physical needs of patients and relatives during these challenging times are addressed by nurses, who are of paramount importance in end-of-life and palliative care. They are in charge of symptom alleviation, pain management, and promoting death with dignity. Nurses make sure that care is focused on the patient by being kind and communicating well. This makes the patient more comfortable and improves their quality of life. This article reviews the many studies on the role of nurses in end-of-life and palliative care. In providing patient-centered, compassionate palliative and end-of-life care, nurses are essential, as this review study emphasizes. During the latter phases of life, their unwavering presence guarantees patients and their families respectful treatment, emotional support, and symptom control. Effective nursing practices are shaped by knowledge, intention, self-efficacy, and supportive care environments. Training programs must emphasize the importance of nursing roles in palliative care to enhance outcomes and quality of life. By addressing holistic needs and fostering open communication, nurses ensure comfort, respect, and dignity for every patient. Strengthening targeted interventions can further improve nursing practices, especially in primary healthcare settings, ensuring equitable, high-quality end-of-life care.